If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(x + -8) + 4 = 2(12) + x Reorder the terms: -1(-8 + x) + 4 = 2(12) + x (-8 * -1 + x * -1) + 4 = 2(12) + x (8 + -1x) + 4 = 2(12) + x Reorder the terms: 8 + 4 + -1x = 2(12) + x Combine like terms: 8 + 4 = 12 12 + -1x = 2(12) + x Multiply 2 * 12 12 + -1x = 24 + x Solving 12 + -1x = 24 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 12 + -1x + -1x = 24 + x + -1x Combine like terms: -1x + -1x = -2x 12 + -2x = 24 + x + -1x Combine like terms: x + -1x = 0 12 + -2x = 24 + 0 12 + -2x = 24 Add '-12' to each side of the equation. 12 + -12 + -2x = 24 + -12 Combine like terms: 12 + -12 = 0 0 + -2x = 24 + -12 -2x = 24 + -12 Combine like terms: 24 + -12 = 12 -2x = 12 Divide each side by '-2'. x = -6 Simplifying x = -6
| 25=10+5j | | 5m^2+26m+5=0 | | 2x-3*-13=9 | | -(x-8)+4=2(-12)+x | | 7x+3(5-3x)=5 | | b+3+b=b+50 | | ly-8l+6=15 | | 3a+1=a+19 | | 15.08+w=30.08 | | Cosx/cos^2(2x) | | -5x-3*-13=30 | | 7m+48=8(m+7) | | 3b^2+11b+8=0 | | -5x-(3*-13)=30 | | 18=5-2+6x-x | | -(x-8)+4=2(7)+x | | x+14=35 | | (r-p)/(x-q)=m | | -5x-(-3*-13)=30 | | 2x-4-6=0 | | 12+[6+(13-7)]2-5= | | 72/4.8=20.4/c | | -(x-8)+4=2(-1)+x | | y+4.3=5.9 | | 42x^2-40x+8=0 | | 5k^2+35k+60=0 | | -(x-8)+4=2(1.25)+x | | 12/x=7/3 | | -(x-8)+4=2(0)+x | | 3(2p+7)=1 | | 7/n=24.5/56 | | 7(1-5r)+6r=94 |